How is the Lives Saved Tool (LiST) used in the global health community? Results of a mixed-methods LiST user study - Angela R. Stegmuller; Andrew Self; Kate Litvin; Timothy Roberton (BMC, 2017)
Abstract Background The Lives Saved Tool (LiST) is a computer-based model that estimates the impact of scaling up key interventions to improve maternal, newborn and child health. Initially developed to inform the Lancet Child Survival Series of 2003, the functionality and scope of LiST have been expanded greatly over the past 10 years. This study sought to "take stock" of how LiST is now being used and for what purposes. Methods We conducted a quantitative survey of LiST users, qualitative interviews with a smaller sample of LiST users and members of the LiST team at Johns Hopkins University, and a literature review of studies involving LiST analyses. Results LiST is being used by donors, international organizations, governments, NGOs and academic institutions to assist program evaluation, inform strategic planning and evidenced-based decision-making, and advocate for high-impact interventions. Some organizations have integrated LiST into internal workflows and built in-house capacity for using LiST, while other organizations rely on the LiST team for support and to outsource analyses. In addition to being a popular stand-alone software, LiST is used as a calculation engine for other applications. Conclusions The Lives Saved Tool has been reported to be a useful model in maternal, newborn, and child health. With continued commitment, LiST should remain as a part of the international health toolkit used to assess maternal, newborn and child health programs.